2004
DOI: 10.1083/jcb.200404171
|View full text |Cite
|
Sign up to set email alerts
|

The syndecan-1 ectodomain regulates αvβ3 integrin activity in human mammary carcinoma cells

Abstract: The αvβ3 integrin participates in cell morphogenesis, growth factor signaling, and cell survival. Activation of the integrin is central to these processes and is influenced by specific ECM components, which engage both integrins and syndecans. This paper demonstrates that the αvβ3 integrin and syndecan-1 (S1) are functionally coupled. The integrin is dependent on the syndecan to become activated and to mediate signals required for MDA-MB-231 and MDA-MB-435 human mammary carcinoma cell spreading on vitronectin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
219
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(229 citation statements)
references
References 73 publications
(93 reference statements)
6
219
1
3
Order By: Relevance
“…The Sdc1 regulates the activities of several integrins, including ␣v␤3, ␣v␤5, and ␤4 integrins. [43][44][45][46] Although the FN matrix assembly appears to be initiated mainly by Arg-Gly-Asp-binding integrin ␣5␤1, 47,48 alternative FN-binding integrin receptors (eg, ␣v␤3, ␣4␤1, and ␣v␤1) can also support this process once properly activated. 33,49 -52 It is possible that Sdc1 induction activates integrins other than ␣5␤1 and initiates an alternative assembly pathway, thus resulting in an ECM that is structurally/compositionally different from that assembled under the control of ␣5␤1.…”
Section: Discussionmentioning
confidence: 99%
“…The Sdc1 regulates the activities of several integrins, including ␣v␤3, ␣v␤5, and ␤4 integrins. [43][44][45][46] Although the FN matrix assembly appears to be initiated mainly by Arg-Gly-Asp-binding integrin ␣5␤1, 47,48 alternative FN-binding integrin receptors (eg, ␣v␤3, ␣4␤1, and ␣v␤1) can also support this process once properly activated. 33,49 -52 It is possible that Sdc1 induction activates integrins other than ␣5␤1 and initiates an alternative assembly pathway, thus resulting in an ECM that is structurally/compositionally different from that assembled under the control of ␣5␤1.…”
Section: Discussionmentioning
confidence: 99%
“…A site within the ectodomain of syndecan-4 interacts with an unidentified surface molecule to promote adhesion without requiring the cytoplasmic domain (36). The integrin ␣v␤3 was shown to be dependent on syndecan-1 for activation and to mediate signals required for human mammary carcinoma cell spread on vitronectin (37). Recently, Whiteford and Couchman (38) have shown that a conserved NXIP motif is required for cell adhesion properties of the syndecan-4 ectodomain.…”
Section: Discussionmentioning
confidence: 99%
“…33 Integrins have heparan-binding domains, which indicate that heparan sulfate proteoglycans may modulate integrin signaling and cell adhesion. 34 Movement/rotation problems in the chondrocytes of the growth plate have been reported in b1-integrin-null mice. 33 The b1-integrin-null growth plates show larger and round-shaped proliferating chondrocytes arranged side by side, possibly reflecting impaired movement and inability to form columns.…”
Section: Cilia In Growth Plate and Osteochondroma Ce De Andrea Et Almentioning
confidence: 99%